Load Balancing Network by using Round Robin Algorithm: A Systematic Literature Review - Hidayat, Taufik; Azzery, Yasep; Mahardiko, Rahutomo (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2019)
The use of load balance on a network will be very much needed if the network is an active network and is widely accessed by users. A reason is that it allows network imbalances to occur. Round Robin (RR) algorithm can be applied for network load balancing because it is a simple algorithm to schedule processes so that it can provide work process efficiency. Authors use the Systematic Literature Review (SLR) method in which it can be applied for criteria selection during papers search to match the title being raised. SLR is divided into five stages, namely formalization of questions, criteria selection, selection of sources, selection of search results, and quality assessment. By using SLR, it is expected that papers according to criteria and quality can be found.